A stent for branch pulmonary artery stenosis after double-lung transplantation in a patient with COVID-19: a case report. Issue 10 (10th August 2021) - Zheng, Qiang; Shang, Xiaoke; Dong, Nianguo; Shi, Jiawei
Abstract: Background: Coronavirus disease 2019 (COVID-19) continues to be a pandemic worldwide. Lung transplantation is the last option to increase life expectancy of end-stage COVID-19 patients. Branch pulmonary artery stenosis (PAS) is a rare complication after lung transplantation with an extremely poor prognosis. The current trend in the management of branch PAS is percutaneous balloon angioplasty and/or stent implantation, rather than high-risk reoperation with a lower success rate. Case summary: The subject was a 54-year-old male with severe acute respiratory syndrome coronavirus 2 infection who underwent a double-lung transplantation. He suffered hypoxaemia and right heart dysfunction following the operation. Right cardiac catheterization and pulmonary angiography examination revealed severe stenosis of the right branch pulmonary artery. Due to immunosuppression and reduced coagulation function, the patient underwent pulmonary artery balloon dilatation and stent implantation, and ultimately recovered well. Discussion: The combination of balloon dilatation and stent implantation is a good alternative to reoperation for patients with COVID-19.